Arctic researches and life among the Esquimaux [electronic resource] : being the narrative of an expedition in search of Sir John Franklin, in the years 1860, 1861 and 1862 - Hall, Charles Francis, 1821-1871. (New York : Harper, 1865)
Added t.p.: Hall's Arctic research expedition and life among the Esquimaux. "With maps and one hundred illustrations." Electronic reproduction. Mode of access: Internet. 44